Green tax reforms with promotion of renewable energy sources and carbon capture and sequestration: Comparison of different alternatives - Susana Silva; Isabel Soares; Carlos Pinho (Energy Reports, 2020)
The need to decarbonize economic production processes is undeniable and has been considered by most countries worldwide. Renewable Energy Sources (RES) and Carbon Capture and Sequestration (CCS) technologies appear among the most promising routes to the decarbonization process. We propose an equilibrium model where final-goods production uses labor and energy, and energy is generated using non-polluting RES and polluting fossil fuels. The government implements a Green Tax Reform (GTR), where it imposes a tax on emissions and uses revenues to finance subsidies to RES and support to CCS technologies. We test how results change according to the priority given to RES or to CCS support. Our results show that prioritizing RES support achieves better economic results and potentially also better environmental results. Overall, our empirical simulation demonstrates that resource substitution has a stronger benefit than decarbonizing fossil fuels.
Keywords: 330; Carbon capture and sequestration; Economy; Environmental policy; Renewable energy sources